The design of a real-time formative evaluation of the implementation process of lifestyle interventions at two worksites using a 7-step strategy (BRAVO@Work) - Wierenga Debbie; Engbers Luuk H; van Empelen Pepijn; Hildebrandt Vincent H; van Mechelen Willem (BMC, 2012)
Abstract Background Worksite health promotion programs (WHPPs) offer an attractive opportunity to improve the lifestyle of employees. Nevertheless, broad scale and successful implementation of WHPPs in daily practice often fails. In the present study, called BRAVO@Work, a 7-step implementation strategy was used to develop, implement and embed a WHPP in two different worksites with a focus on multiple lifestyle interventions. This article describes the design and framework for the formative evaluation of this 7-step strategy under real-time conditions by an embedded scientist with the purpose to gain insight into whether this this 7-step strategy is a useful and effective implementation strategy. Furthermore, we aim to gain insight into factors that either facilitate or hamper the implementation process, the quality of the implemented lifestyle interventions and the degree of adoption, implementation and continuation of these interventions. Methods and design This study is a formative evaluation within two different worksites with an embedded scientist on site to continuously monitor the implementation process. Each worksite (i.e. a University of Applied Sciences and an Academic Hospital) will assign a participating faculty or a department, to implement a WHPP focusing on lifestyle interventions using the 7-step strategy. The primary focus will be to describe the natural course of development, implementation and maintenance of a WHPP by studying [a] the use and adherence to the 7-step strategy, [b] barriers and facilitators that influence the natural course of adoption, implementation and maintenance, and [c] the implementation process of the lifestyle interventions. All data will be collected using qualitative (i.e. real-time monitoring and semi-structured interviews) and quantitative methods (i.e. process evaluation questionnaires) applying data triangulation. Except for the real-time monitoring, the data collection will take place at baseline and after 6, 12 and 18 months. Discussion This is one of the few studies to extensively and continuously monitor the natural course of the implementation process of a WHPP by a formative evaluation using a mix of quantitative and qualitative methods on different organizational levels (i.e. management, project group, employees) with an embedded scientist on site. Trial Registration NTR2861